Stratified and nonstratified areas in the North Sea: Long‐term variability and biological and policy implications. Issue 7 (3rd July 2015) - van Leeuwen, Sonja; Tett, Paul; Mills, David; van der Molen, Johan
Abstract The European Unions' Marine Strategy Framework Directive aims to limit anthropogenic influences in the marine environment. But marine ecosystems are characterized by high variability, and it is not trivial to define its natural state. Here, we use the physical environment as a basis for marine classification, as it determines the conditions in which organisms must operate to survive and thrive locally. We present a delineation of the North Sea into five distinct regimes, based on multidecadal stratification characteristics. Results are based on a 51 year simulation of the region using the coupled hydrobiogeochemical model GETM‐ERSEM‐BFM. The five identified regimes are: permanently stratified, seasonally stratified, intermittently stratified, permanently mixed, and Region Of Freshwater Influence (ROFI). The areas characterized by these regimes show some interannual variation in geographical coverage, but are overall remarkable stable features within the North Sea. Results also show that 29% of North Sea waters fail to classify as one of the defined stratification regimes, due to high interannual variability. Biological characteristics of these regimes differ from diatom‐based food webs in areas with prolonged stratification to Phaeocystis‐dominated food webs in areas experiencing short‐lived or no stratification. The spatial stability of the identified regimes indicates that carefully selected monitoring locations can be used to represent a substantive area of the North Sea.